Perceptions of users and preparers towards corporate internet reporting: Evidence from an emerging market - Ahmed Hassan Ahmed; Mohamed E. Elmaghrabi; Omar Ali Alhassoon; Ahmed Diab (Cogent Business & Management, 2023)
AbstractThis study investigates the perceptions of users and preparers of corporate financial information on Corporate Internet Reporting (CIR) practices adopted by firms listed on the Egyptian Exchange (EGX). Theoretically, this study employs a decision-usefulness theoretical framework. Methodologically, a survey was conducted using a questionnaire to gather opinions on internet infrastructure, using the Internet for disclosure reasons in Egypt, and the qualitative attributes of beneficial accounting information. The findings show that most of the participants were satisfied with the investigated issues, but there were significant differences in opinions among respondent groups regarding the security and privacy of internet dissemination. The participants regarded hard-copy annual reports as the primary source of corporate financial disclosure in Egypt, and CIR practices were seen as complementary to hard-copy reports. Additionally, the study found that CIR could improve the quality of accounting information according to the IASB Framework, except for verifiability. The study’s findings hold potential significance for Egyptian regulators and standard-setters responsible for supporting accounting standards applicable to internet disclosures. Disseminating knowledge about CIR practices to concerned groups, such as investors, academicians, regulators, standard-setters, and business organizations, is crucial, given the lack of research into the views of concerned groups regarding CIR practices. The current research seeks to fill this limitation by eliciting responses from users and preparers in Egypt.